2021
DOI: 10.3390/genes12091313
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Inflammatory Responses in the Context of Physical Activity

Abstract: Epigenetic modifications occur in response to environmental changes and play a fundamental role in the regulation of gene expression. PA is found to elicit an inflammatory response, both from the innate and adaptive divisions of the immunological system. The inflammatory reaction is considered a vital trigger of epigenetic changes that in turn modulate inflammatory actions. The tissue responses to PA involve local and general changes. The epigenetic mechanisms involved include: DNA methylation, histone protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 151 publications
0
9
0
Order By: Relevance
“…In other inflammatory diseases, the general view is that regular moderate-intensity physical activity could have an anti-inflammatory effect, while prolonged or high-intensity PA can trigger inflammation, both by leading to epigenetic changes that, in turn, regulate inflammatory responses in peripheral tissues [ 305 , 306 , 307 ]. These peripheral epigenetic changes appear to be largely induced by the muscle secretome, also known as “myokinome”, which corresponds to all the cytokines or proteins produced by the myocyte in response to muscular contractions [ 308 , 309 ]. These sport-induced epigenetic modulations (including both DNA methylations, histone modifications and miR modulations [ 309 ]) seem to vary according to the type of performed exercise (and the frequency, the intensity and the duration) [ 309 ]; the individual (in terms of age, gender and body composition) [ 305 , 309 ] and can vary from one tissue to another [ 310 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other inflammatory diseases, the general view is that regular moderate-intensity physical activity could have an anti-inflammatory effect, while prolonged or high-intensity PA can trigger inflammation, both by leading to epigenetic changes that, in turn, regulate inflammatory responses in peripheral tissues [ 305 , 306 , 307 ]. These peripheral epigenetic changes appear to be largely induced by the muscle secretome, also known as “myokinome”, which corresponds to all the cytokines or proteins produced by the myocyte in response to muscular contractions [ 308 , 309 ]. These sport-induced epigenetic modulations (including both DNA methylations, histone modifications and miR modulations [ 309 ]) seem to vary according to the type of performed exercise (and the frequency, the intensity and the duration) [ 309 ]; the individual (in terms of age, gender and body composition) [ 305 , 309 ] and can vary from one tissue to another [ 310 ].…”
Section: Resultsmentioning
confidence: 99%
“…These peripheral epigenetic changes appear to be largely induced by the muscle secretome, also known as “myokinome”, which corresponds to all the cytokines or proteins produced by the myocyte in response to muscular contractions [ 308 , 309 ]. These sport-induced epigenetic modulations (including both DNA methylations, histone modifications and miR modulations [ 309 ]) seem to vary according to the type of performed exercise (and the frequency, the intensity and the duration) [ 309 ]; the individual (in terms of age, gender and body composition) [ 305 , 309 ] and can vary from one tissue to another [ 310 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tarnowski et al ( Tarnowski et al, 2021 ) have reported epigenetics changes at the level of inflammatory response after exercise, while Denham and others ( Denham et al, 2016 ) conducted a clinical trial and assessed the epigenetics modifications in a sample of eight young (aged 21.1 ± 2.2 years) men after 8 weeks of a program of resistance exercise training. Authors reported changes in methylation patterns of genes related to cellular and biological processes such as axon guidance, diabetes and metabolic impairments, and immunity as well as CpG islands, in more detail, growth factor genes—growth-hormone releasing hormone (GHRH) and fibroblast growth factor type 1 (FGF-1).…”
Section: Sports Epigenetics/epigenomicsmentioning
confidence: 99%
“…Furthermore, exercise exerts short-term transient effects on epigenetic targets [330,331] and seems to have a wider epigenetic impact in the long term during exercise training [332][333][334]. Physical activity (PA) elicits an inflammatory reaction that triggers epigenetic changes [335] that include DNA and histone modifications, as well as the expression of specific microRNAs, and thus can induce specific and fine-tuned changes to the transcriptional response [336].…”
Section: Sedentarity and Exercise As Epigenetic Programmers Of Variou...mentioning
confidence: 99%